2021
DOI: 10.3390/insects12040276
|View full text |Cite
|
Sign up to set email alerts
|

From Global to Local—New Insights into Features of Pyrethroid Detoxification in Vector Mosquitoes

Abstract: The threat of mosquito-borne diseases continues to be a problem for public health in subtropical and tropical regions of the world; in response, there has been increased use of adulticidal insecticides, such as pyrethroids, in human habitation areas over the last thirty years. As a result, the prevalence of pyrethroid-resistant genetic markers in natural mosquito populations has increased at an alarming rate. This review details recent advances in the understanding of specific mechanisms associated with pyreth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 199 publications
0
10
0
Order By: Relevance
“…12,13 Mosquitoes have been found to be metabolically resistant to several insecticides used in public health programs, such as pyrethroids, organophosphorus, carbamates, and organochlorines. 14,15 In cases of metabolic resistance, mosquitoes prevent or slow down the arrival of insecticides to the target site by metabolic detoxification, isolation, or accelerated excretion involving enhanced expression and activity of relevant metabolic detoxification enzymes. 15 Metabolic detoxification enzymes in insects, which can function independently or synergistically, include primarily cytochrome P450 (CYP450), carboxylesterase, glutathione S-transferase (GST), ABC transporter, and uridine diphosphate glycosyltransferase proteins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Mosquitoes have been found to be metabolically resistant to several insecticides used in public health programs, such as pyrethroids, organophosphorus, carbamates, and organochlorines. 14,15 In cases of metabolic resistance, mosquitoes prevent or slow down the arrival of insecticides to the target site by metabolic detoxification, isolation, or accelerated excretion involving enhanced expression and activity of relevant metabolic detoxification enzymes. 15 Metabolic detoxification enzymes in insects, which can function independently or synergistically, include primarily cytochrome P450 (CYP450), carboxylesterase, glutathione S-transferase (GST), ABC transporter, and uridine diphosphate glycosyltransferase proteins.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In cases of metabolic resistance, mosquitoes prevent or slow down the arrival of insecticides to the target site by metabolic detoxification, isolation, or accelerated excretion involving enhanced expression and activity of relevant metabolic detoxification enzymes. 15 Metabolic detoxification enzymes in insects, which can function independently or synergistically, include primarily cytochrome P450 (CYP450), carboxylesterase, glutathione S-transferase (GST), ABC transporter, and uridine diphosphate glycosyltransferase proteins. [16][17][18][19] In mosquitoes, CYP450 proteins participate in a series of physiological and biochemical reactions, including the regulation of endogenous substances such as hormones and steroids and metabolic detoxifying exogenous substances such as pesticides and plant toxins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This task is performed by odorant binding proteins (OBPs) in vertebrates and two small soluble protein families, OBPs and chemosensory proteins (CSPs), in insects . CSPs were first discovered in Drosophila melanogaster in 1994, and they have been found in many insect species since then. , Due to their specificity in insects, the miscellaneous functions of CSPs are thought to be abundant in insects . A large number of studies have shown that insect CSPs can detect and selectively bind to volatiles, chemical compounds, and sex pheromone analogues in the external environment, as well as solubilize and carry endogenous hormones and nutrients …”
Section: Introductionmentioning
confidence: 99%
“…: the L1014F mutation), increased metabolic detoxi cation activity/e cacy (e.g. P450 monooxygenases), cuticular thickening or changing in hydrocarbon content and binding/sequestration mechanisms [19][20][21][22][23][24][25][26][27][28][29][30]. Furthermore, some vector species exhibit different forms of behavioural resistance (or behavioural plasticity) comprising changes in biting behaviour that facilitate the avoidance of the insecticidal barrier, such as exibility in the spectrum of host choice (opportunistic behaviour) and/or blood feeding at places and times when humans are less likely to be protected by nets (i.e.…”
Section: Introductionmentioning
confidence: 99%